Spatial coding defects of hippocampal neural ensemble calcium activities in the triple-transgenic Alzheimer's disease mouse model - Xiaoxiao Lin (Elsevier, 2022)
Alzheimer's disease (AD) causes progressive age-related defects in memory and cognitive function and has emerged as a major health and socio-economic concern in the US and worldwide. To develop effective therapeutic treatments for AD, we need to better understand the neural mechanisms by which AD causes memory loss and cognitive deficits. Here we examine large-scale hippocampal neural population calcium activities imaged at single cell resolution in a triple-transgenic Alzheimer's disease mouse model (3xTg-AD) that presents both amyloid plaque and neurofibrillary pathological features along with age-related behavioral defects. To measure encoding of environmental location in hippocampal neural ensembles in the 3xTg-AD mice in vivo, we performed GCaMP6-based calcium imaging using head-mounted, miniature fluorescent microscopes (“miniscopes”) on freely moving animals. We compared hippocampal CA1 excitatory neural ensemble activities during open-field exploration and track-based route-running behaviors in age-matched AD and control mice at young (3–6.5 months old) and old (18–21 months old) ages. During open-field exploration, 3xTg-AD CA1 excitatory cells display significantly higher calcium activity rates compared with Non-Tg controls for both the young and old age groups, suggesting that in vivo enhanced neuronal calcium ensemble activity is a disease feature. CA1 neuronal populations of 3xTg-AD mice show lower spatial information scores compared with control mice. The spatial firing of CA1 neurons of old 3xTg-AD mice also displays higher sparsity and spatial coherence, indicating less place specificity for spatial representation. We find locomotor speed significantly modulates the amplitude of hippocampal neural calcium ensemble activities to a greater extent in 3xTg-AD mice during open field exploration. Our data offer new and comprehensive information about age-dependent neural circuit activity changes in this important AD mouse model and provide strong evidence that spatial coding defects in the neuronal population activities are associated with AD pathology and AD-related memory behavioral deficits.